Analysis of Ecological Criteria for Traditional Housing and Its Adaptation to New Housing Design - Gündoğdu, Ebubekir; Birer, Emel (Scuola Pitagora Editrice, Piazza Santa Maria Degli Angeli, 1, Napoli, 80132, Italy, 2015)
Various characteristics of traditional architecture, such as environment friendly, use of local and natural materials, energy saving, became important for contemporary ecological architecture. Currently, most of the contemporary buildings in Mersin, which lack local technology, cause the distortion of nature and environment, and high energy consumption on the contrary. In 19th century, Mersin was a small port town, though; it turned to be a metropolis today. The rapid growth of Mersin caused the loss of traditional houses, and mass production of apartment blocks that can be rapidly constructed and consumed. After the fast urbanization in Mersin there have remained a very small group of traditional houses, still existing in Mersin city centre and these houses preserve their ecological qualities. This study aims to examine traditional housing in Mersin, in terms of ecological aspects, revealing the relationship between the ecological architecture and vernacular housing technologies of Mersin, and developing some references for their adaptation to new housing design. For the case study, thirty traditional houses located in Mersin city centre, which have not been restored, have been chosen. Observation, trips, photography, checklists and drawings were the methods used for the analyses and the results were evaluated by the help of the charts and diagrams.
Keywords: Traditional housing; Mersin; ecology; sustainability; new housing